2009
DOI: 10.1681/asn.2008121225
|View full text |Cite
|
Sign up to set email alerts
|

Epac Regulates UT-A1 to Increase Urea Transport in Inner Medullary Collecting Ducts

Abstract: Urea plays a critical role in the concentration of urine, thereby regulating water balance. Vasopressin, acting through cAMP, stimulates urea transport across rat terminal inner medullary collecting ducts (IMCD) by increasing the phosphorylation and accumulation at the apical plasma membrane of UT-A1. In addition to acting through protein kinase A (PKA), cAMP also activates Epac (exchange protein activated by cAMP). In this study, we tested whether the regulation of urea transport and UT-A1 transporter activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 40 publications
2
31
1
Order By: Relevance
“…EPAC signaling in response to cAMP agonists has previously been demonstrated in renal epithelial cells. 55 In contrast, in the presence of PC1-p30, increased levels of cAMP lead to STAT3 activation mediated by Src ( Figure 6B). Similarly, in the presence of PC1-p30, EGFR/Src-mediated STAT3 activation is amplified ( Figure 6A).…”
Section: Discussionmentioning
confidence: 93%
“…EPAC signaling in response to cAMP agonists has previously been demonstrated in renal epithelial cells. 55 In contrast, in the presence of PC1-p30, increased levels of cAMP lead to STAT3 activation mediated by Src ( Figure 6B). Similarly, in the presence of PC1-p30, EGFR/Src-mediated STAT3 activation is amplified ( Figure 6A).…”
Section: Discussionmentioning
confidence: 93%
“…10,11 IM-PTECs were preloaded with 5-(and-6)-carboxy-29,79-dichlorodihydrofluorescein diacetate (DCF-DA), which is converted into fluorescent DCF via oxidation by radicals. 18 After hypoxia, reoxygenation was induced by addition of fresh medium to the cells. Reoxygenation induced a rapid increase in probe conversion ( Figure 1A), indicating fast accumulation of cytosolic ROS.…”
Section: Activation Of Epac By 8-pcpt-29-o-me-camp Reduces Productionmentioning
confidence: 99%
“…A recent study has also implicated the MEK-ERK pathway in regulating UT-A phosphorylation in response to forskolin in rat IMCD. 28 To test whether extracellular signal-regulated kinase (ERK) mitogen-activated protein (MAP) kinase is involved in regulating UT-A phosphorylation, isolated rat IMCD samples were incubated with dDAVP in the presence or absence of 10 M MEK1/2 (map kinase kinase 1 and 2) inhibitor U0126. Immunoblotting for phosphorylated ERK (pERK) demonstrated that dDAVP treatment did not increase ERK phosphorylation and that U0126 significantly blocked ERK phosphorylation in both control and dDAVP-treated samples ( Figure 9, A and F).…”
Section: Regulation Of ␤-Catenin Phosphorylation By Ddavpmentioning
confidence: 99%